The mediator role of KM process for creative organizational learning case study: Knowledge based companies. Issue 3 (10th August 2015) - Bagheri, Rouhollah; Hamidizadeh, Mohhamad Reza; Sabbagh, Parisa
Abstract : Purpose: – The current study aims to investigate the existing relationship between knowledge management (KM) infrastructures, KM process capabilities, creative organizational learning (OL) and organizational performance. Design/methodology/approach: – Statistical population includes executives of knowledge-based companies in Tehran Science and Technology Park of Iran. The 68 questionnaires were distributed among the census, of which 60 questionnaires were completed correctly. The research data were analyzed by SPSS and PLS software. The unit of analysis is a company that has adopted a knowledge management system (KMS). Target population of the research consisted of 85 top managers of knowledge-based companies in Tehran Science and Technology Park of Iran ( N = 85). Random sampling method was applied in this study, and 71 top managers were considered as the statistical sample based on the "Morgan Table". One standard five-point Likert questionnaire was adopted and distributed between top managers in the park; 62 questionnaires were returned, among which 60 were statistically investigated. The structural relations among variables were tested using the partial least squares method. Findings: – This study shows that the KM processes can mediate between creative OL and factors in the KM infrastructure. The results of the study demonstrate that KM process capabilities have the most crucial role in creative OL. The results indicate a significant influence of the infrastructure capabilities on the process capabilities, also the impacts of KM process capabilities on creative OL and the impacts of creative OL on organizational performance was confirmed. Research limitations/implications: – Using a holistic view of the KM performance framework, this study has provided insights to KM for researchers because it explains the integrated aspects of KM performance by examining the relationships between the KM infrastructure, knowledge process capabilities, and organizational outcomes. Previous studies on KM have been fragmented because they only consider some aspects of KM performance rather than using a holistic view of the KM performance framework: they have examined the relationship between one or two facets of KM enablers and process capability, or between KM process capabilities and organizational performance. Practical implications: – In order to manage rapid change and global competition in business environments, knowledge workers should create new business opportunities and continuously question what and how they can contribute to these chances. Organizational KMS should support the learning processes of their knowledge workers. Social implications: – The continuous learning and experiments are necessary in order to produce new ideas and products: it is critical to emphasize the importance of a KM infrastructure that supports and encourages learning in organizations. The creative learning in turn affects organizational performance indicating that without learning, organizations cannot overcome the boundary of old business practices and adjust to change in environments. Originality/value: – Previous researches did not appraise the effect of KM and its capabilities on organizational performance, and the specific influence of creative OL was disregarded. The present study demonstrates the mechanism of KM effect on organizational performance and describes the comprehensive dimensions of KM performance.